AB1098 STRUCTURAL ELEMENTS OF THE KNEE ENTHESES ASSESSED IN HEALTHY SUBJECTS WITH ULTRA HIGH FIELD MRI (150 MICRONS). (2nd June 2020) - Roche, D.; Michel, C.; Daudé, P.; Le Troter, A.; Chagnaud, C.; Mattei, J. P.; Pini, L.; Guye, M.; Bendahan, D.; Guis, S.
Abstract : Background: Fibrocartilaginous enthesis is composed of different histological zones which are commonly referred to the tendon distal extremity (a lamellar tissue with a low cell density, collagen and connective tissue), the fibrocartilaginous zone (with chondrocytes), a progressively mineralized zone and the bone. The MRI visualization of the water content of entheses is challenging given the very short relation time so that entheses has been very poorly assessed using MRI (1). Objectives: The main objective of the study was to assess the structural elements of the knee enthesis based on the quantitative T2* measurements using Ultra High Field (UHF) MRI. Methods: Twelve healthy subjects without any osteoarticular pathology were included in the study after they provided their informed consent. 3D gradient echo sequence with a 4.3 ms echo time and T2* mapping were performed. The lateral internal, external and crossed ligaments, patellar and quadricipital tendons were assessed. T2* measurements were performed specifically on the quadricipital tendon. Results: The quadricipital tendon and the bone trabeculation could be visualized on the UHF MR image. The T2* mapping analysis illustrated a large value (16.4 ± 4 ms) for the subchondral bone and much lower values for the trabecular bone (11 ± 4.5 ms) and the different zones of the keen entheses (7.7 ± 1.9 ms). Conclusion: Based on T2* measurements performed using UHF MRI, the different structural elements of the knee entheses were distinguished. This quantitative stratification could be used to assess changes in pathological conditions such as SpA and trauma. References: [1]Benjamin M, Bydder GM. Magnetic resonance imaging of entheses using ultrashort TE (UTE) pulse sequences. Journal of magnetic resonance imaging: JMRI. 2007;25(2):381-9. Disclosure of Interests: None declared